De leprosário a favela: violação de direitos humanos e racismo ambiental na Comunidade Colônia Getúlio Vargas em Bayeux/PB - Silva, Josildo dos Santos (2019)
The objective of this study was to analyze the stigma and environmental racism in the Colônia Getúlio Vargas Community located in the buffer zone of the Xem-Xem State Forest Conservation Unit, in the municipality of Bayeux / PB. The specific objectives were to investigate the policy of compulsory isolation in Brazil from the Leprosarium Colônia Getúlio Vargas, to identify the demands for environmental justice and to interpret the identity relationship of the inhabitants of the said community with the territory of the environmental reserve, where a lifestyle and ideas about their appropriation. Regarding the methodological procedures for the systematization of this work, this occurred in three complementary moments: document review, bibliographical research and field research. We have recourse to the history of the present time through orality, making use of the semistructured interview and the notes in field notebooks. Empirical research pointed out that the population has a sense of belonging to this territory, they presented in the narratives a memory permeated by stigma around the disease "leprosy" / hanseníase. The experiences with the community made me understand that environmental racism is expressed through environmental injustices, social exclusion, stigmata about the former Leprosarium, and, above all, the prejudice mentioned by representatives of the State in relation to the practices of the Sacred Jurema